Defective expression of T cell-associated glycoprotein in severe combined immunodeficiency. - Jung, L K (1986)
A T cell surface membrane-associated glycoprotein, Tp40 (40,000 mol wt), also designated as CD-7, was not expressed by the T cells of a patient with severe combined immunodeficiency. In addition to this abnormality, T cell proliferative responses to mitogens were defective and the IL-2 receptor expression was deficient on the patient's T lymphocytes. However, his T cells were found to provide help for the differentiation of normal B cells to Ig-secreting cells. Abundant circulating B cells were detected. These B cells proliferated normally in the presence of anti-mu antibodies and B cell growth factors, but did not differentiate into antibody-secreting cells when provided with the help of normal T cells. In addition, his activated B cells did not proliferate to IL-2 even though IL-2 receptors were expressed. A successful allogeneic histocompatible bone marrow transplantation resulting in T cell engraftment corrected both the T and B cell immunodeficiencies. These findings support the hypothesis that the Tp40 deficiency present in this patient is related to a defect of the T cell precursors, and that Tp40 plays important roles not only essential to T cell interactions but also to certain aspects of T-B cell interaction during the early lymphoid development.